\[\boxed{\text{443\ (443).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ 2a^{5}b^{2} - 4a^{3}b + 6a^{2}b^{3} =\]
\[= 2a^{2}b \cdot \left( a^{3}b - 2a + 3b^{2} \right).\]
\[2)\ mn^{3} + 5m^{2}n^{2} - 7m^{2}n =\]
\[= mn \cdot \left( n^{2} + 5mn - 7m \right).\]
\[3)\ xy^{2} + x^{2}y - xy =\]
\[= xy \cdot (y + x - 1).\]
\[4)\ 9x^{3} + 4x^{2} - x =\]
\[= x \cdot \left( 9x^{2} + 4x - 1 \right).\]
\[5) - 6m^{4} - 8m^{5} - 2m^{6} =\]
\[= - 2m^{4} \cdot \left( 3 + 4m + m^{2} \right).\]
\[6)\ 42a^{4}b - 28a^{3}b^{2} - 70a^{5}b^{3} =\]
\[= 7a^{3}b \cdot \left( 6a - 4b - 10a^{2}b^{2} \right)\text{.\ }\]
\[\boxed{\text{443.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[= 5n + 10 = 5 \cdot (n + 2) -\]
\[делится\ на\ 5.\]
\[2)\ 2n + (2n + 2) + (2n + 4) =\]
\[= 2n + 2n + 2 + 2n + 4 =\]
\[= 6n + 6 =\]
\[= 6 \cdot (n + 1) - делится\ на\ 6.\]
\[= 8 \cdot (n + 2) - делится\ на\ 8.\]
\[= 4n + 6 =\]
\[= 4 \cdot (n + 1) + 2 - делится\ на\ \]
\[4\ и\ остаток\ 2.\]
\[= 5n + 10 + n + 5 =\]
\[= 6n + 15 = 6n + 12 + 3 =\]
\[= 6 \cdot (n + 2) + 3 - делится\ на\ \]
\[6\ и\ остаток\ 3.\ \]